2017
DOI: 10.4172/2252-5211.1000288
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Cultural Solution to the Challenge of Waste Generation at Individual Level: Case Study from India

Abstract: Introduction Importance of the themeThe human being is distinguished from an animal through his culture. The culture of humans is well defined in the customs, traditions and rituals prevalent in any society throughout the globe. None of the indigenous culture is away from the nature's rule. The eco-concepts are primary feature of every culture of the human society. There should not be second thought in stating that every nation of the world had rich traditions embedded in the ethics of protecting nature. Histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…Moreover, waste problems have become interesting businesses managed by the community organizations to change the community's logical thinking to be more aware of their own environment. This finding supports the study conducted by Crociata et al (2015), Mehra (2017), and Roberts and Okereke (2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, waste problems have become interesting businesses managed by the community organizations to change the community's logical thinking to be more aware of their own environment. This finding supports the study conducted by Crociata et al (2015), Mehra (2017), and Roberts and Okereke (2017).…”
Section: Discussionsupporting
confidence: 92%
“…The role of local culture in the community-based waste management is to unite the community feelings and local identities. Evidence has shown that waste management based on local culture can encourage pro-environmental behavior (Crociata et al, 2015;Mehra, 2017;Roberts & Okereke, 2017). Thus, the involvement of local knowledge and culture is needed to strengthen the community-based waste management.…”
Section: Concept Of Community-based Waste Managementmentioning
confidence: 99%